PEMANFAATAN EKSTRAK KULIT BUAH NAGA MERAH DAN EKSTRAK JAHE MERAH DALAM PEMBUATAN MINUMAN BUBUK INSTAN - Victor David; Noviar Harun; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research was to obtain the best formulation of extract red pitaya peels and extract making red ginger in instant powder drinks. The method used in this research was a complete random design with 4 treatments and 4 replications. The treatments were P1 (90% red pitaya peel extracts : 10% red ginger extracts), P2 (80% red pitaya peel extracts : 20% red ginger extracts), P3 (70% red pitaya peel extracts : 30% red ginger extracts), P4 (60% red pitaya peel extracts : 40% red ginger extracts). The results show that the usage red pitaya peel extracts and red ginger extracts significantly influenced the moisture content, ash content, total sugar content, antioxidant content, descriptive value of taste, aroma, texture and color of instant powder. The best treatment was P4 (60% red pitaya peel extracts : 40% red ginger extracts) with moisture content of 2.53%, ash content 0.77%, total sugar content 64.77%, antioxidant activity 104.58 ppm, descriptive sensory of taste 4.80, aroma 4.40, texture 3.97, color 2.83 and over all acceptance test 4.11.Keyword : instant powder, quality, red pitaya peel, red ginger.